Assessing IQ in adolescents with mild to moderate cerebral palsy using the WISC-V. Issue 7 (3rd October 2022) - Coceski, Monika; Hocking, Darren R.; Reid, Susan M.; Abu-Rayya, Hisham M.; Reddihough, Dinah S.; Wrennall, Jacquie; Stargatt, Robyn
Abstract: Objective: To examine the influence of subtests that require fine motor responses on measures of intellectual ability, and compare three approaches to minimizing motor demands while assessing cognitive abilities in adolescents with cerebral palsy (CP) to the traditional method of the Wechsler Intelligence Scale for Children – Fifth edition (WISC-V). Method: Seventy adolescents with CP ( M  = 14 years 6 months, SD  = 10 months) who were able to provide either a verbal or point response were assessed using the WISC-V administered via Q-interactive. The pencil-to-paper version of Coding was also administered. Performance on Block Design and pencil-to-paper Coding was compared to Visual Puzzles and Coding on Q-interactive, respectively. Full Scale IQ (FSIQ) scores derived according to the Traditional method of the WISC-V were compared to alternative estimates of FSIQ derived according to the Q-interactive, Nonmotor, and Motor-free methods, which minimized motor demands. Results: An additional 7–12% of participants were able to respond to Visual puzzles and Coding on Q-interactive compared to Block Design and pencil-to-paper Coding, respectively, and performance was marginally but significantly better. For 54 adolescents (Gross Motor Function Classification System (GMFCS) Level I-III) who were able to obtain FSIQ scores, the Traditional method underestimated FSIQ by 3–6 points compared to the alternative methods and the difference was most pronounced for those with more severe CP as measured by the GMFCS. Conclusion: Adolescents with CP are at an inherent disadvantage when cognitive ability is assessed using the Traditional method of the WISC-V. Findings suggest clinicians should employ the Nonmotor or Motor-free methods when assessing IQ in adolescents with CP.